Software Industry Insights: A Financial Dive into Airbnb, Uber, and Lyft - Yang, Mengyuan (Transactions on Economics, Business and Management Research, 2024)
This paper’s topic is related to the software industry’s investment potential and risks, and it focuses on three prominent technology companies: Airbnb, Uber, and Lyft. The paper also provides a comprehensive analysis of these companies through various financial indicators, including risk, profitability ratios, and market ratios. It assesses the financial stability and market performance using metrics such as market capitalization, beta, debt ratio, and current ratio, revealing each company’s risk profile. The profitability part contains the profit margin, return on assets (ROA), and return on equity (ROE), showing companies’ earning capabilities. Furthermore, market ratios such as price-to-earnings (P/E), price-to-book (P/B), dividend yield, PEG, and momentum offer insights into the companies’ valuation and investor sentiment. The paper concludes with an investment selection table that categorizes the companies based on the preferences of different types of investors, including value, income, PEG, index, ratio analysis, and momentum, providing a strategic overview for making informed investment decisions in the dynamic software industry landscape.